The Role of Leaders' Motivational Words in Improving Employee Performance in the Public Sector - Suprianto, Suprianto; Ramli, Ramli; Rosary, A. Osfira (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This study examines how the role of leader motivational speech affects employee performance in the public sector, specifically exploring whether it increases employee motivation and productivity. Using a mixed methods approach, the study includes qualitative and quantitative data, such as employee performance metrics, survey results on perceived motivation, and analysis of how leaders communicate. This is a desk study that combines current research on how leader motivational speech can improve employee performance in the public sector. Data collection is done by exploring various relevant research results. The results show that when leaders use motivational speech effectively, it is associated with better employee morale and performance, indicating that it is an important motivational tool. that studies on leader motivational speech show that it has a significant impact on improving employee performance, especially in the public sector. The study shows that leader speech increases intrinsic motivation, leading to a more engaged and satisfied workforce. This is supported by the fact that 78% of participants stated that their job satisfaction increased due to motivational efforts. The issue of how different motivational strategies affect employee performance is addressed by uncovering how it works, specifically by promoting a positive organizational culture and better communication between teams. The findings of this study are important both academically and practically; These findings add to the current body of knowledge on public service motivation by providing a clearer view of the emotional and psychological aspects that drive employee engagement. In addition, public sector leaders can use this information to develop strategies that use motivational words as a cost-effective way to improve workforce productivity and morale. Ultimately, this study adds to the conversation about the effectiveness of leadership in improving employee performance by providing evidence that can guide policies and training efforts to improve employee performance through better motivational practices.